179k views
5 votes
What is the solution to 8x minus 3(2x minus 4) = 3(x minus 6)

User Neel Gala
by
5.6k points

2 Answers

5 votes

Answer:

x = 30.

Explanation:

8x - 3(2x - 4) = 3(x - 6)

8x - 3*2x + - 3*-4 = 3*x + 3 * -6

8x - 6x + 12 = 3x - 18

2x + 12 = 3x - 18

2x - 3x + 12 = 3x - 3x - 18

-x + 12 = -18

-x + 12 - 12 = -18 - 12

-x = -33

-x/-1 = -30/-1

x = 30.

User IdemeNaHavaj
by
6.2k points
4 votes

Answer:


x=30

Explanation:


8x-3\left(2x-4\right)=3\left(x-6\right)

First, we will expand
-3\left(2x-4\right) by applying the distributive property:


-3* \:2x-\left(-3\right)* \:4

**
-\left(-a\right)=a


-6x+12


8x-6x+12=3\left(x-6\right)

Expand,
3\left(x-6\right):


3x-3* \:6


3x-18


2x+12=3x-18

Subtract 12 from both sides:


2x+12-12=3x-18-12


2x=3x-30

Subtract 3x from both sides:


2x-3x=3x-30-3x


-x=-30

Divide both sides by -1:


(-x)/(-1)=(-30)/(-1)


x=30

________________________

User Vinnydiehl
by
5.3k points